“Livability” and “Ungratefulness”: A Refugee Critique of the Law and Humanitarianism - Yến Lê Espiritu; Ma Vang (Social Inclusion)
Critical refugee studies (CRS) conceptualizes refugees’ lived experience as a site of theory‐making and knowledge production with and for refugees. As co‐founders of the Critical Refugee Studies Collective (CRSC), and as scholars with refugee backgrounds, we theorize alongside our refugee partners to offer a refugee critique of refugee law and humanitarianism. Departing from the 1951 Refugee Convention definition of “refugee,” whose restrictive legal and historical framing cannot account for the complex conditions that displace human beings, we offer the concept of “livability” to name the mundane, creative, and fearless possibilities of living that undergird refugees’ claims to move audaciously. Furthermore, departing from humanitarian narratives that expect refugees to be forever thankful for having been rescued, we propose the concept of “ungratefulness” to describe refugee refusal to exhibit gratitude and deference for the space they have been allowed. Our critique emerged from sustained engagement with refugee partners through in‐person and virtual gatherings organized by the CRSC. Together, we argue that livability and ungratefulness constitute examples of “epistemic disobedience” of the colonial and unilateral knowledge production about refugees, as they call attention to distinctly discernible refugee agency and epistemology that break with the historically appointed role of refugees as seen entirely through a lens of precarity and gratitude.